استعمال سديلة العضلة النعلية في تغطية عظم الظنبوب المكشوف - ملحم, فراس (Latakia University Journal -Medical Sciences Series, 2017)
خلال العقدين الأخيرين تمّ إحراز تقدّم كبير في مجال تدبير رضوح الطرفين السفليين إلى الحدّ الذي سمح بإنقاذ الكثير من الأطراف من البتر. يعتبر نقل العضلات الطريقة المثالية في علاج الضياعات المادية الواسعة الشاملة للنسج الرخوة في رضوح الأطراف في حال انكشاف العظم. الهدف من دراستنا هذه هو تحرّي الفعالية العلاجية لإصلاح الضياعات المادية في كسور القسم المتوسط من الظنبوب مع انكشاف العظم باستعمال السديلة العضلية المعنقة للنصف الأنسي للعضلة النعلية. قمنا بدراسة استرجاعية لعشر حالات عانت من كسور مفتوحة خضعت لترميم النسج الرخوة باستخدام التكنيك المذكور بين عاميّ 2013 و2016 في مشفى الأسد الجامعي باللاذقية. كانت النتائج الترميمية لهذا التكنيك الجراحي ممتازة. تمثّل سديلة العضلة النعلية بنصفها الأنسي خياراً هامّاً لترميم الضياعات الماديّة في الثلث المتوسط من الساق مع انكشاف عظم الظنبوب . يتمّ المحافظة على وظيفة العضلة النعلية. إنّ قوس دوران السديلة الطويل نسبيّاً يجعلها قادرةً على ترميم الضياعات المادية ذات القياسات والأشكال المختلفة في الثلث المتوسط من الساق مع انكشاف عظم الظنبوب. العملية سهلة نسبيّاً. يمكن للعضلة أن تملأ الجوف الضيّق و أن ترمّم العيب المادي في الوقت ذاته. تعتبر الأذية في الموقع المعطي قليلة الأهميّة. The management of lower extremity trauma has evolved over the last two decades to the point that many extremities that would have required amputation are routinely salvaged. The use of transposition muscle is regarded as the optimal method for the treatment of extensive defects of soft tissues in limb traumatology. The aim of the study is to investigate the therapeutic effect of repairing soft tissue defects of mid-tibia open fractures with muscle flap pedicled with medial half of soleus. A retrospective study of our outcome of 10 performed soft-tissue reconstruction of an open tibial wound cases. All these patients were operated using the proposed surgical technique between 2013 and 2015 in AL-ASSAD University Hospital in Lattakia, Syria. The results of this technique of reconstruction are excellent. Medial hemisoleus flap is a valuable option for soft tissue coverage of middle third of lower leg. It does not sacrifice the whole function of the Soleus muscle. Due to its longer arc of rotation, this flap can cover the defects of different size and shape in middle third of leg. The operation is relatively easy. The muscle can fill the narrow cavity and repair the soft tissue defect simultaneously. The donor-site injury is minor.